2019
DOI: 10.1177/1933719118815590
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Changes in Maternal Peripheral Blood Correlate With Time-to-Delivery in Pregnancies Complicated by Premature Prelabor Rupture of the Membranes

Abstract: Premature prelabor rupture of the membranes (PPROM) causes one-third of preterm births worldwide and is most likely caused by subclinical intrauterine infection and/or inflammation. We proposed that women with systemic inflammation at the time of PPROM would have shorter latency. Peripheral blood samples were collected from 20 singleton pregnant women with PPROM between 23 ± 1 and 33 ± 6 weeks. The first sample was drawn within 48 hours of admission, followed by weekly blood draws until delivery. Pregnancies c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…pPROM is the rupture of the membrane before the onset of labor before 37 weeks of gestation and accounts for one-third of all PTBs [ 37 ]. High levels of pro-inflammatory cytokines such as interleukin (IL)1RA, IL-1β, IL-6, tumor necrosis factor α (TNF- α), monocyte chemotactic protein-1 have been reported in the plasma of pregnant women with pPROM [ 38 ]. In a previous investigation of ours, cytokine levels in the vaginal fluid were higher among pregnant women who delivered preterm with pPROM and PTL compared to women with term deliveries [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…pPROM is the rupture of the membrane before the onset of labor before 37 weeks of gestation and accounts for one-third of all PTBs [ 37 ]. High levels of pro-inflammatory cytokines such as interleukin (IL)1RA, IL-1β, IL-6, tumor necrosis factor α (TNF- α), monocyte chemotactic protein-1 have been reported in the plasma of pregnant women with pPROM [ 38 ]. In a previous investigation of ours, cytokine levels in the vaginal fluid were higher among pregnant women who delivered preterm with pPROM and PTL compared to women with term deliveries [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…We observed in PTB increased CXCL9 levels, a chemokine known for attracting Th1 lymphocytes to an inflamed site, 35 which is in contrast to another recent work. 36 In the latter study, the PTB group included solely women with preterm premature rupture of membranes (PPROM) as oppose to our cohort in which only 46%…”
Section: Discussionmentioning
confidence: 99%
“…There were also reports of DEHP-induced interleukin-1 secretion in mononuclear cells and in babies born to mothers who suffered from prenatal infection and inflammation (Calo et al, 1993;De Felice et al, 1999, 2002Yang et al, 2000). Case-control studies to study preterm birth in pregnant women revealed that increased levels of ADAMTS (A Disintegrin and Metalloproteinase with Thrombospondin Motifs) family-ADAMTS4, ADAMTS5 and proinflammatory cytokines like interleukin (IL)-6, and tumor necrosis factor-α (TNF-α) in mid-trimester amniotic fluid associated with spontaneous preterm delivery (Ronzoni et al, 2018;Melekoglu et al, 2019). These data suggest that the toxicity of periconception phthalate exposure and phthalates' capacity to disrupt pregnancy and birth via endocrine and inflammatory pathways impact development and health across the lifespan.…”
Section: Studies Of Dna Methylation In Placental Tissuementioning
confidence: 99%